Ｒefinement and Modification of ZL114 Alloy by ＲE Ce - FU Yuan-ke; DU Yi-han; DUAN Hong-yang; HAN Wei-chao; ZHOU Qiang (Journal of Harbin University of Science and Technology)
ZL114 alloy is a hypoeutectic Al-Si alloy with high strength，high toughness and thermal cracking resistance. It is widely used in aerospace and automotive fields. By the use of metallurgical microscope，scanning electron microscope and tensile testing machine，this paper studies the refinement and modification of Zl114 alloy by Al-5Ti-1B( 1wt. % ) and different Ce contents. The results show that with the increase of Ce contents，the primary α-Al phase is gradually refined，the distribution tends to be uniform and the morphology of eutectic silicon turns from needle flake to granular and short rod. Fracture surface turns fine at first and then coarse. The number of tearing edges increases at first and then decreases，and the cracks between the tearing edges become deeper at first and shallower later. The fracture is always brittle. The ultimate tensile strength and elongation increase at first and then decrease. When Ce content is 0. 07wt. % ，the ultimate tensile strength and elongation reach the maximum value of 183. 2 MPa and 5. 936% ，respectively.